2012
DOI: 10.1136/oemed-2012-100689
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for new onset and persistence of multi-site musculoskeletal pain in a longitudinal study of workers in Crete

Abstract: Objectives-To explore occupational and psychological risk factors for the incidence and persistence of multi-site musculoskeletal pain.Methods-We conducted a longitudinal investigation of three occupational groups in Crete, Greece. Baseline information was obtained at interview about pain in the past year at each of six anatomical sites, and about possible risk factors for subsequent symptoms. Twelve months later, subjects were re-interviewed about pain at the same anatomical sites in the past month. Pain at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
7
21
3
Order By: Relevance
“…Similar findings have also been reported in other studies exploring risk factors for MSP 9 11 19 33. Solidaki et al 33 reported that physical loading was associated with persistence of MSP among occupational groups in Crete. Notably, physical strain also predicted the pathway of developing MSP where the number of pain sites increased from less than one at baseline to more than three at the last follow-up in our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar findings have also been reported in other studies exploring risk factors for MSP 9 11 19 33. Solidaki et al 33 reported that physical loading was associated with persistence of MSP among occupational groups in Crete. Notably, physical strain also predicted the pathway of developing MSP where the number of pain sites increased from less than one at baseline to more than three at the last follow-up in our study.…”
Section: Discussionsupporting
confidence: 84%
“…High-perceived physical workload was a strong predictor of a high MSP trajectory among female kitchen workers in Finland 15. Similar findings have also been reported in other studies exploring risk factors for MSP 9 11 19 33. Solidaki et al 33 reported that physical loading was associated with persistence of MSP among occupational groups in Crete.…”
Section: Discussionsupporting
confidence: 77%
“…Particularly, for high and vibrational demands occupations, associations were stronger as we increased the threshold of the number of painful anatomical regions, which is in agreement with previous evidence in long-term workers (46,47). These findings suggest that, from the earliest stages of employment, high demands may rapidly produce musculoskeletal pain in more than one body region (particularly in the neck/ shoulder and upper-/lower-back areas, ie, the regions most frequently reported as painful).…”
Section: Discussionsupporting
confidence: 81%
“…The main pre-existing conditions in our population were metabolic diseases in 18.5%, hypertension (9.1%), hypothyroidism (4.7%) and depression (1.8%). In our study, there was no significant relationship between the pre-existence of comorbidities and the majority of MSD, which is inconsistent with some studies (25,26). According to some authors, and extending beyond the organic pathologies considered to be at risk of MS-MSD, personality type may interfere with the appearance of these lesions.…”
Section: Multivariate Studycontrasting
confidence: 99%
“…In this study, 90% of patients were in job stress situations significantly correlated with MS-MSD involvement. Similar findings have been described by some authors (25,43 (45). The complexity of explanatory models makes it difficult to determine occupational risk factors for MSD.…”
Section: Multivariate Studysupporting
confidence: 86%